Combined transcriptomic and metabolomic analysis of alginate oligosaccharides alleviating salt stress in rice seedlings - Du, You-Wei; Liu, Ling; Feng, Nai-Jie; Zheng, Dian-Feng; Liu, Mei-Ling; Zhou, Hang; Deng, Peng; Wang, Ya-xing; Zhao, Hui-Min (BMC plant biology, 2023)
Background Salt stress is one of the key factors limiting rice production. Alginate oligosaccharides (AOS) enhance plant stress resistance. However, the molecular mechanism underlying salt tolerance in rice induced by AOS remains unclear. FL478, which is a salt-tolerant indica recombinant inbred line and IR29, a salt-sensitive rice cultivar, were used to comprehensively analyze the effects of AOS sprayed on leaves in terms of transcriptomic and metabolite profiles of rice seedlings under salt stress. Results In this experiment, exogenous application of AOS increased SOD, CAT and APX activities, as well as GSH and ASA levels to reduce the damage to leaf membrane, increased rice stem diameter, the number of root tips, aboveground and subterranean biomass, and improved rice salt tolerance. Comparative transcriptomic analyses showed that the regulation of AOS combined with salt treatment induced the differential expression of 305 and 1030 genes in FL478 and IR29. The expressed genes enriched in KEGG pathway analysis were associated with antioxidant levels, photosynthesis, cell wall synthesis, and signal transduction. The genes associated with light-trapping proteins and RLCK receptor cytoplasmic kinases, including CBA, LHCB, and Lhcp genes, were fregulated in response to salt stress. Treatment with AOS combined with salt induced the differential expression of 22 and 50 metabolites in FL478 and IR29. These metabolites were mainly related to the metabolism of amino and nucleotide sugars, tryptophan, histidine, and β -alanine. The abundance of metabolites associated with antioxidant activity, such as 6-hydroxymelatonin, wedelolactone and L-histidine increased significantly. Combined transcriptomic and metabolomic analyses revealed that dehydroascorbic acid in the glutathione and ascorbic acid cycles plays a vital role in salt tolerance mediated by AOS. Conclusion AOS activate signal transduction, regulate photosynthesis, cell wall formation, and multiple antioxidant pathways in response to salt stress. This study provides a molecular basis for the alleviation of salt stress-induced damage by AOS in rice.